Evaluation of Pencak Silat Achievement Development in Central Lampung Regency - Saputra, Adi; Ariesna, Rachmat Dody; Aprilianto, Dwi (STKIP Al Islam Tunas Bangsa dan HEPI, 2025)
The Indonesian Pencak Silat Association (IPSI) Central Lampung Branch is an organization that plays an important role in developing and preserving pencak silat at the regional level. This study focuses on revealing how IPSI Central Lampung trains athletes using a descriptive evaluative method through the CIPP (Context, Input, Process, and Product) model approach. The research population involved IPSI administrators, coaches, and pencak silat athletes who are active in coaching activities. The sampling technique used was purposive sampling, which involves selecting informants who are considered to have in-depth and relevant knowledge of the research problem, supplemented by snowball sampling, in which the initial informants recommend other individuals who can be the next data sources. Data analysis shows that the role of the government, both in the form of moral and material support, is crucial to the development of athletes' achievements, especially in pencak silat, which requires serious attention in terms of continuous coaching. However, the results of the study also confirm that the coaching program run by IPSI Central Lampung is still not fully systematic, periodic, and structured, thus potentially hindering the achievement of optimal performance. Therefore, concrete efforts are needed to improve the quality of coaching, including through continuous program planning, improving the competence of coaches, and providing adequate facilities and infrastructure. With a more focused strategy and cross-sector support, the process of coaching pencak silat athletes in Central Lampung is expected to produce athletes who excel at the regional and national levels.